Implantación de un sistema contable de costos para una mejor administración productiva y financiera de la fábrica la Avelina, período 2011 - Vásconez Gutiérrez, Abelinda Marisol (2013)
The present research was to carry out a careful study for the IMPLEMENTATION OF A COST FOR THE AVELINA MILK FACTORY “ABELLITO S.A.”, making consideration the true cost of the production process pasteurized milk taking into accounting all the elements the cost as: raw material/Materials, Labor and Manufacturing Overhead Costs. The research that was used for the development of the thesis is so applied through the descriptive research is handling experimental method, using as the unit of study the universe using the theoretical methods, empirical and statistical as: inductive- deductive, analytical- synthetic, synthetic- structural, working with papers and among the techniques used were the survey which was directed to the Production staff in order to finder levant information to the production, as well a show to take the accounting records according to their activity, the interview was conducted Administrative Staff; what will allow to search about the organizational aspect of the enterprise and the observation that was applied in all stages of the production of the pasteurized milk, which facilitate the decision-making. Based on this research work could reach the conclusion that it was necessary to apply a cost system that yields results that allow the company to adequately manage its production processes at the same time make good decisions and comparison of financial statements.